Sclerosing composition

The curable composition, featuring (meth)acryloyl compounds, saccharin, and cationic catalysts, addresses the challenges of balancing crosslinking and controlling delayed curability in cationic polymerizable systems, achieving stable and adjustable delayed curing times for various applications.

JP7648909B2Active Publication Date: 2025-03-19THREE BOND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021561458
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-11-25
Publication Date
2025-03-19
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

Existing curable compositions based on cationic polymerizable compounds, such as epoxy compounds, face challenges in balancing the degree of crosslinking promotion by cationic catalysts and suppression by retardants, and in controlling delayed curability due to limited raw material options.

Method used

A curable composition comprising compounds with (meth)acryloyl groups, saccharin as a retardant, and either a photocationic catalyst or a thermal cationic catalyst, which ensures delayed curing time after irradiation or heating, regardless of the transparency of the adherend.

Benefits of technology

The composition achieves stable and controllable delayed curing properties, allowing for operations like bonding and tightening after a specific time post-irradiation or heating, with a delayed curing time ranging from 30 seconds to 10 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648909000011
    Figure 0007648909000011
  • Figure 0007648909000001
    Figure 0007648909000001
  • Figure 0007648909000002
    Figure 0007648909000002
Patent Text Reader

Abstract

The present invention provides a curable composition which can ensure a delayed curing time for operations such as bonding or tightening after heating or irradiating the curable composition with energy rays regardless of whether an adherend is transparent, and then can develop the delayed curability. The present invention is a curable composition containing components (A) to (C). Component (A): Compound having a (meth)acryloyl group in a molecule Component (B): Saccharin Component (C): At least one among a photocationic catalyst as a component (C-1) and a thermal cationic catalyst as a component (C-2).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition having delayed curing properties in which curing does not begin when the composition is irradiated with active energy rays (energy rays) or heated, but rather cures after a specific time has elapsed after the end of irradiation or heating. Hereinafter, the term "delayed curing properties" refers to a composition that is uncured immediately after the end of energy ray irradiation or heating, but cures after a specific time has elapsed after the end of energy ray irradiation or heating, and the specific time is referred to as "delayed curing time." [Background technology]

[0002] It has been known that epoxy compounds and the like have a curing property when irradiated with light in the presence of a cationic catalyst. It is known that a delayed-curing composition that does not cure immediately after irradiation with energy rays but cures after a certain time has elapsed can be obtained by adding a polyalcohol compound, a polyether compound, and a plasticizer as a retarder to an epoxy compound and a cationic catalyst (JP 2018-159069 A, corresponding to the specification of US Patent Application Publication No. 2020 / 0040131). Summary of the Invention

[0003] However, in a delayed curing composition such as that described in JP 2018-159069 A, it is difficult to balance the degree of crosslinking promotion by the cationic catalyst and the degree of crosslinking inhibition by the retarder.

[0004] In addition, the types of raw materials for cationically polymerizable compounds such as epoxy compounds are limited compared to the types of radically polymerizable compounds such as (meth)acrylate compounds. The raw materials affect the curability of the composition depending on the number of functional groups, main skeleton, modification, etc., so there is a problem that it is particularly difficult to control delayed curability in a composition based on a cationically polymerizable compound with limited types of raw materials.

[0005] The present invention has been made in view of the above circumstances, and has an object to provide a curable composition which can ensure a delayed curing time for performing operations such as lamination and fastening after irradiation with energy rays or heating, regardless of whether an adherend is transparent or not, and which can thereafter exhibit delayed curability.

[0006] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have discovered a method relating to a curable composition, leading to the completion of the present invention.

[0007] The gist of the present invention will now be described. A first embodiment of the present invention is a curable composition comprising the following components (A) to (C): Component (A): A compound having a (meth)acryloyl group in the molecule (B) Ingredient: Saccharin Component (C): A photocation catalyst as component (C-1).

[0008] A second embodiment of the present invention is a curable composition comprising the following components (A) to (C): Component (A): A compound having a (meth)acryloyl group in the molecule (B) Ingredient: Saccharin Component (C): Component (C-2) is a thermal cationic catalyst.

[0009] A third embodiment of the present invention is a curable composition comprising the following components (A) to (C): Component (A): A compound having a (meth)acryloyl group in the molecule (B) Ingredient: Saccharin Component (C): A photocationic catalyst as component (C-1) and a thermal cationic catalyst as component (C-2).

[0010] A fourth embodiment of the present invention is the curable composition according to any one of the first to third embodiments, further comprising a radical polymerization accelerator as component (D).

[0011] A fifth embodiment of the present invention is the curable composition according to the fourth embodiment, wherein the component (D) is an amine compound other than the component (B).

[0012] A sixth embodiment of the present invention is the curable composition according to any of the first to fifth embodiments, which does not comprise an organic peroxide.

[0013] A seventh embodiment of the present invention is the curable composition according to the first embodiment, which is uncured immediately after the end of the irradiation of energy rays and is cured after a specific time has elapsed after the end of the irradiation of energy rays.

[0014] An eighth embodiment of the present invention is the curable composition according to the second embodiment, which is uncured immediately after the end of heating, and is cured after a specific time has elapsed after the end of heating.

[0015] A ninth embodiment of the present invention is the curable composition according to the third embodiment, which is uncured immediately after the end of energy ray irradiation or heating, and is cured after a specific time has elapsed after the end of energy ray irradiation or heating.

[0016] A tenth embodiment of the present invention is the curable composition according to any of the seventh to ninth embodiments, wherein the specific time is from 30 seconds to 10 hours.

[0017] An eleventh embodiment of the present invention is a curing method comprising applying the curable composition according to the seventh or ninth embodiment to an adherend, and then irradiating the curable composition with energy rays.

[0018] A twelfth embodiment of the present invention is a method for curing, comprising applying the curable composition according to the eighth or ninth embodiment to an adherend, and then heating the curable composition. [Brief description of the drawings]

[0019] [Figure 1]FIG. 1 shows a method for pressing a test piece with a certain force to confirm the onset of delayed curing properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention relates to a curable composition comprising the following components (A) to (C): Component (A): A compound having a (meth)acryloyl group in the molecule (B) Ingredient: Saccharin Component (C): At least one of a photocationic catalyst as component (C-1) and a thermal cationic catalyst as component (C-2).

[0021] According to the curable composition of the present invention, regardless of whether the adherend is transparent or not, it is possible to ensure a delayed curing time for performing operations such as lamination and fastening after irradiation with energy rays or heating, and thereafter the delayed curing property can be expressed.

[0022] The present invention will be described in detail below. The component (A) that can be used in the present invention is a compound having a (meth)acryloyl group in the molecule. The component (A) may be any compound having a (meth)acryloyl group in the molecule, and examples thereof include, but are not limited to, (meth)acrylic oligomers, (meth)acrylic monomers, and (meth)acrylamide monomers. The (meth)acryloyl group is a general term for acryloyl groups and methacryloyl groups, and (meth)acrylic acid ester compounds are also called (meth)acrylates.

[0023] Examples of (meth)acrylic oligomers include, but are not limited to, epoxy-modified (meth)acrylic oligomers, urethane-modified (meth)acrylic oligomers, and oligomers having a main skeleton obtained by polymerizing (meth)acrylic monomers and having a (meth)acryloyl group at the end of the main skeleton. Specific examples include so-called urethane-modified (meth)acrylic oligomers synthesized by reacting a polyfunctional isocyanate with a polyhydric polyol and a compound having a (meth)acryloyl group and a hydroxyl group. The polyhydric polyol may have various skeletons, and those having an ethylene oxide skeleton, a polyester skeleton, a polyether skeleton, a polybutadiene skeleton, a hydrogenated polybutadiene skeleton, or the like can be used. In addition, examples of epoxy-modified (meth)acrylic oligomers obtained by adding (meth)acrylic acid to bisphenol A type epoxy resin, bisphenol F type epoxy resin, or phenol novolac resin include, but are not limited to, these.

[0024] As the (meth)acrylic monomer used for forming the main skeleton of the oligomer having a main skeleton obtained by polymerizing a (meth)acrylic monomer and having a (meth)acryloyl group at the end of the main skeleton, a monofunctional monomer having one (meth)acryloyl group in the molecule is preferable. Specific examples thereof include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, and (meth) t-Butyl acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, toluyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, Examples of the acrylates include, but are not limited to, 3-methoxybutyl, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, γ-(methacryloyloxypropyl)trimethoxysilane, ethylene oxide adducts of (meth)acrylic acid, trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethylmethyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethylmethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, and 2-perfluorohexadecylethyl (meth)acrylate. In the present invention, the (meth)acrylic monomer can be selected from the above-mentioned (meth)acrylic monomers and is preferably a (meth)acrylic monomer having a hydrocarbon group.

[0025] The weight average molecular weight of the oligomer having a main skeleton obtained by polymerizing a (meth)acrylic monomer and a (meth)acryloyl group at the end of the main skeleton is, for example, 1000 or more, preferably 5000 to 40000. In particular, when the weight average molecular weight is 5000 or more, the elasticity of the cured product tends to be easily expressed, and the cured product is less likely to crack in a heat resistance test, which is preferable. On the other hand, when the weight average molecular weight is 40000 or less, the viscosity does not become too high, so that stringiness is less likely to occur when the curable composition is applied, which is preferable. The oligomer having a main skeleton obtained by polymerizing a (meth)acrylic monomer and a (meth)acryloyl group at the end of the main skeleton can be obtained by various polymerization methods, and the method is not particularly limited, but a radical polymerization method is preferable from the viewpoint of versatility of the monomer and ease of reaction control. Among radical polymerizations, controlled radical polymerization is preferable, living radical polymerization is more preferable, and atom transfer radical polymerization is particularly preferable. Methods for introducing (meth)acryloyl groups into a polymer of a (meth)acrylic monomer, which is the main skeleton, include (1) a method of reacting a vinyl polymer having a hydroxyl group at the end with a chlorine, bromine, or hydroxyl group-containing (meth)acrylate compound, (2) a method of reacting a vinyl polymer having a halogen group at the end with an alkali metal ion or a quaternary ammonium ion-containing (meth)acrylate compound, and (3) a method of reacting a vinyl polymer having a hydroxyl group at the end with a diisocyanate compound, and reacting the remaining isocyanate group with a hydroxyl group-containing (meth)acrylate, etc. These methods are already known and are described in JP-A-61-133201, JP-A-11-80250, JP-A-2000-38404, JP-A-2001-271055, JP-A-2002-69121, etc. In addition, oligomers that have a main skeleton formed by polymerizing (meth)acrylic monomers and have a (meth)acryloyl group at the end of the main skeleton have the property of not changing or losing their flexibility even in high-temperature atmospheres such as at 100°C or high-temperature, high-humidity atmospheres such as at 85°C x 85% RH.

[0026] It is preferable that the epoxy-modified (meth)acrylic oligomer and the urethane-modified (meth)acrylic oligomer also have a molecular weight of 1,000 or more.

[0027] In the present invention, a (meth)acrylic monomer can also be used as the (A) component. In order to adjust the viscosity of the curable composition to be low and improve workability, a (meth)acrylic oligomer and a (meth)acrylic monomer can be mixed, or a (meth)acrylic oligomer or a (meth)acrylic monomer can be used alone. In the present invention, from the viewpoint of more effectively expressing delayed curing properties, it is preferable that 50 parts by mass or more of 100 parts by mass of the (A) component is a (meth)acrylic monomer, more preferably 80 parts by mass or more of the (meth)acrylic monomer, and even more preferably 100 parts by mass of the (meth)acrylic monomer. As the (meth)acrylic monomer, in addition to a monofunctional monomer, a bifunctional monomer, a trifunctional monomer, or a polyfunctional monomer having 4 or more functionalities can be mentioned. From the viewpoint of more easily controlling the delayed curing time, it is preferable that the (meth)acrylic monomer contains a bifunctional monomer, a trifunctional monomer, or a polyfunctional monomer having 4 or more functionalities.

[0028] Particularly preferably, the component (A) contains a low molecular weight (meth)acrylic monomer having a molecular weight of less than 1000, since the addition of the component (A) has the effect of lowering the viscosity of the curable composition. When two or more types of compounds having (meth)acryloyl groups in the molecule are used as the component (A), it is more preferable that all of them are low molecular weight (meth)acrylic monomers having a molecular weight of less than 1000.

[0029] In the curable composition of the present invention, the (meth)acrylic monomer preferably contains an acrylic monomer since the time required for curing is short.

[0030] Specific examples of monofunctional monomers include lauryl (meth)acrylate, stearyl (meth)acrylate, ethyl carbitol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, adamantanyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxytetraethylene glycol (meth)acrylate, nonylphenoxyethyl (meth)acrylate, nonylphenoxytetraethylene glycol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxyethyl (meth)acrylate, butoxytriethylene glycol (meth)acrylate, 2- Ethylhexyl polyethylene glycol (meth)acrylate, 4-hydroxybutyl (meth)acrylate, nonylphenyl polypropylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, glycerol (meth)acrylate, polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, epichlorohydrin-modified butyl (meth)acrylate, epichlorohydrin-modified phenoxy (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and the like, but are not limited thereto.

[0031] Preferred monofunctional monomers are (meth)acrylic monomers having a hydroxyl group in the molecule and / or (meth)acrylic monomers having a saturated alicyclic structure. Specific examples of (meth)acrylic monomers having a hydroxyl group include, but are not limited to, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, and 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate. Most preferred are 2-hydroxypropyl methacrylate and / or 2-hydroxyethyl methacrylate. Specific examples of (meth)acrylic monomers having a saturated alicyclic structure include, but are not limited to, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, and adamantanyl (meth)acrylate. Most preferred is a (meth)acrylic monomer having an isobornyl skeleton and / or a dicyclopentanyl skeleton. According to one embodiment of the present invention, component (A) contains both the (meth)acrylic monomer having a hydroxyl group in the molecule and the (meth)acrylic monomer having a saturated alicyclic structure.

[0032] Specific examples of bifunctional monomers include 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexane glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethylene oxide (hereinafter abbreviated as EO)-modified neopentyl glycol di(meth)acrylate, propylene oxide (hereinafter abbreviated as P Examples of the ethylene glycol di(meth)acrylate include, but are not limited to, ethylene glycol modified neopentyl glycol di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, caprolactone modified hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, dicyclopentenyl di(meth)acrylate, EO modified dicyclopentenyl di(meth)acrylate, diacryloyl isocyanurate, and EO modified bisphenol A di(meth)acrylate.

[0033] Specific examples of trifunctional monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, ethylcyclohexane (ECH)-modified trimethylolpropane tri(meth)acrylate, ECH-modified glycerol tri(meth)acrylate, tris(acryloyloxyethyl)isocyanurate, and ethylene oxide-modified di(meth)acrylate with isocyanuric acid, but are not limited thereto.

[0034] Specific examples of polyfunctional monomers having 4 or more functionalities include, but are not limited to, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.

[0035] Examples of (meth)acrylamide monomers that can be used in the present invention include, but are not limited to, dimethylacrylamide, acryloylmorpholine, diethylacrylamide, etc. Considering the cost and availability, diethylacrylamide or dimethylacrylamide is preferred. Specific examples of (meth)acrylamide monomers include, but are not limited to, DMAA (registered trademark), ACMO (registered trademark), DEAA (registered trademark), etc., manufactured by KJ Chemicals Co., Ltd.

[0036] The component (B) that can be used in the present invention is saccharin, which is a compound represented by the following formula 1.

[0037] [ka]

[0038] The amount of the (B) component added is preferably 0.1 to 5.0 parts by mass, more preferably 0.1 to 3.0 parts by mass, per 100 parts by mass of the (A) component. When the (B) component is 0.1 part by mass or more, delayed curing properties are more effectively exhibited, and when the (B) component is 5.0 parts by mass or less, storage stability is improved and the delayed curing time can be easily ensured. When two or more types of compounds are used as the (A) component, the amount of the (B) component added per 100 parts by mass of the total amount is preferably within the above range.

[0039] The component (C) that can be used in the present invention is a cationic catalyst. Any compound that generates an acid when irradiated with energy rays (component (C-1): photo-cationic catalyst) or a compound that generates an acid when heated (component (C-2): thermal cationic catalyst) can be used as component (C). In addition, component (C) may be sold in a form dissolved or dispersed in a solvent or plasticizer, and these may also be used.

[0040] As the (C) component, either the (C-1) component or the (C-2) component may be used alone, or the (C-1) component and the (C-2) component may be used in combination. When the curable composition of the present invention contains the (C-1) component, the curable composition can be cured by irradiation with energy rays. On the other hand, when the curable composition of the present invention contains the (C-2) component, the curable composition can be cured by heating. The (C-1) component and the (C-2) component may each be used alone or in combination of two or more.

[0041] Specific photocation catalysts include salts of cationic species such as iodonium cationic species and sulfonium cationic species, and anionic species such as phosphorus anionic species, boron anionic species, antimony anionic species, arsenic anionic species, or sulfonic acid anionic species, and can be used alone or in combination of two or more.Specific examples of the photocation catalysts include, but are not limited to, those having succinimidyl camphorsulfonate, succinimidyl phenylsulfonate, succinimidyl toluylsulfonate, succinimidyl trifluoromethylsulfonate, phthalimidyl trifluorosulfonate, naphthalimidyl camphorsulfonate, naphthalimidyl methanesulfonate, naphthalimidyl trifluoromethanesulfonate, naphthalimidyl toluylsulfonate, and norbornenimidyl trifluoromethanesulfonate as anionic species.

[0042] One example of a sulfonium salt that can be used as a photocation catalyst in the present invention is a compound represented by the following formula 2, where R - Examples of anions include hexafluoroantimonate, tetrafluoroborate, hexafluorophosphate, hexafluoroarsenate, hexachloroantimonate, trifluoromethanesulfonate ion, and fluorosulfonate ion.

[0043] [ka]

[0044] Commercially available photocation catalysts include CPI-100P, CPI-101P, CPI-110B, CPI-200K, CPI-210S, IK-1, and IK-2 manufactured by San-Apro Co., Ltd.; WPI-113, WPI-116, WPI-169, WPI-170, WPAG-336, WPAG-367, WPAG-370, WPAG-469, and WPAG-638 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; and ADEKA Corporation's ADEKA Examples of silicone rubbers that can be used include, but are not limited to, Optomer SP-103, SP-150, SP-151, SP-170, SP-171, SP-172, etc.; Polyset's PC-2506, PC-2508, PC-2520, etc.; San-Aid SI-60, SI-80, SI-100, SI-60L, SI-80L, SI-100L, SI-L145, SI-L150, SI-L160, SI-L110, SI-L147, etc.; and Bluestar Silicones HK's BLUESIL (registered trademark) PI2074.

[0045] As the thermal cationic catalyst, a thermal cationic polymerization initiator containing an amine salt can be used. The thermal cationic polymerization initiator is a compound that generates cationic species by heating. For example, a thermal cationic polymerization initiator containing a salt having a quaternary ammonium cation can be used. In particular, a salt consisting of a quaternary ammonium cation and a borate anion, a salt consisting of a quaternary ammonium cation and an antimony anion, and a salt consisting of a quaternary ammonium cation and a phosphate anion are preferred, and a salt consisting of a quaternary ammonium cation and a borate anion and a salt consisting of a quaternary ammonium cation and an antimony anion are particularly preferred because of their excellent low-temperature curing properties.

[0046] The borate anion may be tetrafluoroborate anion, tetrakis(perfluorophenyl)borate anion, etc. The antimony anion may be tetrafluoroantimony anion, tetrakis(perfluorophenyl)antimony anion, etc. The phosphate anion may be hexafluorophosphate anion, trifluoro[tris(perfluoroethyl)]phosphate anion, etc.

[0047] Commercially available thermal cationic catalysts include, but are not limited to, CXC-1612, CXC-1821, and the like, which are part of the K-PURE (registered trademark) series manufactured by King Industries.

[0048] It is preferable that 0.01 to 5.0 parts by mass of the (C) component be added per 100 parts by mass of the (A) component. When the (C) component is 0.01 part by mass or more, the delayed curing property is more effectively expressed, and when the (C) component is 5.0 parts by mass or less, the storage stability is improved and the delayed curing time can be easily ensured. When two or more types of compounds are used as the (A) component, it is preferable that the amount of the (C) component added per 100 parts by mass of the total amount is in the above range. When two or more types of compounds are used as the (C) component, it is preferable that the total amount is in the above range.

[0049] The curable composition of the present invention may further include a radical polymerization accelerator as component (D). A radical polymerization accelerator is a compound that accelerates the reaction of component (A). Although the cause is not clear, in the present invention, even though there is no raw material that generates radical species, component (A) undergoes radical polymerization to cure the composition, and component (D) has the effect of accelerating the polymerization. In the curable composition of the present invention, component (D) can be added as a curing accelerator within a range that does not impair storage stability. Specific examples of the (D) component include tertiary amines such as 1,2,3,4-tetrahydroquinoline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, diisopropanol-p-toluidine (N,N-di(2-hydroxypropyl)-p-toluidine), and triethylamine; polyamines such as diethylenetriamine, triethylenetetramine, and pentaethylenehexamine; and thioureas such as thiourea, ethylenethiourea, benzoylthiourea, acetylthiourea, and tetramethylthiourea, but are not limited thereto. In addition, the (D) component may be used alone or in combination of two or more types. Here, when the (D) component is an amine compound, a compound other than the (B) component is selected as the (D) component.

[0050] It is preferable that 0.01 to 5.0 parts by mass of the (D) component is added per 100 parts by mass of the (A) component. When the (D) component is 0.01 part by mass or more, the delayed curing time can be appropriately shortened, and when the (D) component is 5.0 parts by mass or less, the delayed curing property can be more effectively exhibited. When two or more types of compounds are used as the (A) component, it is preferable that the amount of the (D) component added per 100 parts by mass of the total amount is within the above range. When two or more types of compounds are used as the (D) component, it is preferable that the total amount is within the above range.

[0051] In the curable composition of the present invention, an organic peroxide may be further added, but it is preferable not to add it in order to more effectively exhibit delayed curing properties. Specifically, the content of the organic peroxide in the curable composition of the present invention is, for example, less than 0.1 parts by mass, and preferably 0.01 parts by mass or less (lower limit: 0 parts by mass), relative to 100 parts by mass of the (A) component (when multiple types of (A) components are used, the total amount is 100 parts by mass). The organic peroxide is a compound in which one or two hydrogen atoms of hydrogen peroxide are substituted with an organic group, such as a hydroperoxide. The hydroperoxide is an organic peroxide having a structure as shown in the following formula 3, where R 1 represents a chain aliphatic hydrocarbon, a cyclic aliphatic hydrocarbon, an aromatic hydrocarbon, or a derivative thereof. Specific examples include, but are not limited to, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide.

[0052] [ka]

[0053] The curable composition of the present invention may further contain a chelating agent, an antioxidant, a polymerization inhibitor and a filler in order to adjust the properties of the curable composition of the present invention and the physical properties of the cured product, to an extent that does not impair the properties of the curable composition of the present invention and the physical properties of the cured product.

[0054] A chelating agent may be further added to the curable composition of the present invention for the purpose of improving storage stability. The means for adding the chelating agent is not particularly limited, and a composition in which a chelating agent that is solid at 25°C is dissolved by a (meth)acrylic monomer that dissolves the chelating agent that is solid at 25°C, or a composition in which a chelating agent that is liquid at 25°C is dissolved by a (meth)acrylic monomer that is compatible with the chelating agent that is liquid at 25°C may be added. When dissolving or dissolving, heating to 30 to 60°C may be performed. The chelating agent is a compound that coordinates with metal ions that are impurities in the curable composition, chelates the metal to inactivate it, and suppresses reactivity in the curable composition. Therefore, the curable composition can maintain its storage stability by adding a chelating agent.

[0055] Specific examples of chelating agents that are solid at 25°C include EDTA·2Na and EDTA·4Na manufactured by Dojin Chemical Laboratory Co., Ltd., and EDTA-based (ethylenediaminetetraacetic acid), NTA-based (nitrilotetraacetic acid), DTPA-based (diethylenetriaminepentaacetic acid), HEDTA-based (hydroxyethylethylenediaminetriacetic acid), TTHA-based (triethylenetetraminehexaacetic acid), PDTA-based (1,3-propanediaminetetraacetic acid), DPTA-OH-based (1,3-diamino-2-hydroxypropanetetraacetic acid), HIDA-based (hydroxyethyliminodiacetic acid), DHEG-based (dihydroxyethylglycine), GEDTA-based (glycol ether diaminetetraacetic acid), CMGA-based (diaboxymethylglutamic acid), EDDS-based ((S,S)-ethylenediaminedisuccinic acid), and EDTMP-based (ethylenediaminetetra(methylenephosphonic acid)) compounds manufactured by Chelest Co., Ltd., but are not limited to these. Specific examples of chelating agents that are liquid at 25°C include, but are not limited to, MZ-8 manufactured by Chelest Co., Ltd., HEDP-based (1-hydroxyethane-1,1-diphosphonic acid), NTMP-based (nitrilotris(methylenephosphonic acid)), and PBTC-based (2-phosphono-1,2,4-butanetricarboxylic acid) compounds. These chelating agents are soluble or compatible with highly polar (meth)acrylic oligomers and (meth)acrylic monomers, but are poorly or completely soluble in low polarity oligomers such as (meth)acrylic oligomers that have a main skeleton formed by polymerizing (meth)acrylic monomers and have (meth)acryloyl groups at the ends of the main skeleton.

[0056] In the curable composition of the present invention, a polymerization inhibitor can be further added to further suppress the viscosity change over time.Specific examples include, but are not limited to, 2,6-di-t-butyl-4-methylphenol, hydroquinone, hydroquinone monomethyl ether, and 4-t-butylcatechol.The concentration of the polymerization inhibitor in the (A) component is preferably 0.01 to 5.0% by mass, and the curability can be maintained if the concentration of the polymerization inhibitor is 5.0% by mass or less.

[0057] Depending on the purpose, an antioxidant may be added. Specific examples of the antioxidant include, but are not limited to, phenol-based antioxidants, thioether-based antioxidants, phosphorus-based antioxidants, and nitroxide-based antioxidants.

[0058] Fillers such as inorganic fillers and organic fillers can be appropriately added to the curable composition of the present invention. By adding a filler, it is possible to adjust not only the viscosity and thixotropy but also the curability and toughness. Examples of inorganic fillers include, but are not limited to, alumina and silica. On the other hand, examples of organic fillers include, but are not limited to, styrene fillers, rubber fillers made of acrylic rubber and polybutadiene rubber, and rubber fillers having a core-shell structure. A particularly preferred inorganic filler is fumed silica. Examples of fumed silica include, but are not limited to, hydrophilic types in which silanol remains on the surface, and hydrophobic types in which the silanol is treated with dimethyldichlorosilane or the like to hydrophobize the silica surface. Specific examples of hydrophilic products include Aerosil (registered trademark) 90, 130, 150, 200, 255, 300, and 380 manufactured by Nippon Aerosil Co., Ltd., and specific examples of hydrophobic products include Aerosil (registered trademark) R972 (treated with dimethyldichlorosilane), R974 (treated with dimethyldichlorosilane), R104 (treated with octamethylcyclotetrasiloxane), R106 (treated with octamethylcyclotetrasiloxane), R202 (treated with polydimethylsiloxane), R805 (treated with octylsilane), R812 (treated with hexamethyldisilazane), R816 (treated with hexadecylsilane), and R711 (treated with methacrylsilane), manufactured by Nippon Aerosil Co., Ltd. Other examples include the Cabosil series, which is a fumed silica manufactured by Cabot Corporation.

[0059] In order to adjust the properties of the curable composition of the present invention and the physical properties of the obtained cured product to an extent that does not impair the properties of the curable composition of the present invention, additives such as a photosensitizer, a silane-based coupling agent, a titanium-based coupling agent, a leveling agent, a plasticizer, and a solvent may be further blended into the curable composition of the present invention.

[0060] The curable composition of the present invention can be produced by a conventionally known method. For example, the curable composition of the present invention can be produced by blending predetermined amounts of the components (A) to (C), and further, if necessary, the component (D), and other components described above, and stirring and mixing them by a conventionally known means. For example, a method can be used in which each component is weighed and charged into a stirring vessel and stirred with a stirrer. Stirring may be performed while vacuum degassing with a vacuum pump. There are no particular limitations on the temperature during stirring and mixing, or the stirring and mixing time. In addition, the curable composition of the present invention is preferably produced in a light-shielded environment.

[0061] The method for applying the curable composition of the present invention to an adherend may be a known method for applying a sealant or adhesive, such as dispensing using an automatic coater, spraying, inkjet printing, screen printing, gravure printing, dipping, spin coating, or the like.

[0062] The curable composition of the present invention can be applied to any material to which the curable composition of the present invention can exhibit adhesive properties, such as metal, resin, ceramic, and glass. The resin may be any of plastic, elastomer, and rubber. In particular, the curable composition of the present invention exhibits excellent delayed curing properties, so that a coating film can be formed after irradiation with active energy rays. In the past, the delayed curing properties were insufficient, so the adherend was limited to a material that transmits active energy rays, and it was necessary to form a coating film before irradiation with active energy rays. However, the curable composition of the present invention can be applied to a material that is opaque to active energy rays, and there is no particular restriction on the adherend, which has the advantage of broadening the range of application.

[0063] Various methods can be used for irradiating energy rays. Energy rays refer to electromagnetic waves or charged particle beams that have an energy quantum, and examples of such methods include light rays and electron beams. For example, ultraviolet rays with a wavelength of about 100 to 400 nm and visible light with a wavelength of about 400 to 800 nm can be suitably used. A high-pressure mercury lamp or an LED can be used as a light source for irradiating energy rays. A belt conveyor type irradiator equipped with a high-pressure mercury lamp can be used, and an integrated light amount of, for example, 0.1 to 60 kJ / m can be used. 2 The illuminance of an LED irradiation device that uses an LED as a light source is generally 30 to 900 mW / cm 2 and in some cases 20-300mW / cm 2 The light irradiation conditions can be adjusted by the type and amount of the raw material contained in the curable composition. Here, the curable composition is uncured immediately after the end of the irradiation of the energy rays, and is cured after a specific time has elapsed after the end of the irradiation of the energy rays, and is said to have "delayed curing properties". The delayed curing time may be, for example, 30 seconds to 10 hours, preferably 30 seconds to 3 hours, and more preferably 30 seconds to 2 hours. If the delayed curing time is 30 seconds or more, a sufficient time can be secured until the delayed curing properties are developed. By securing the time until the delayed curing properties are developed, operations such as lamination, tightening, and fixing can be performed. In addition, if the delayed curing time is 10 hours or less, the curing can proceed more efficiently. In addition, it is preferable from the viewpoint of the line tact in the production line.

[0064] Various methods can be used for heating. Specific examples include a hot air drying oven and an IR oven, and for example, heating can be performed at 40 to 100°C for 10 seconds to 24 hours. Heating conditions can be adjusted according to the type and amount of raw materials contained in the curable composition. Here, the curable composition is said to be "having delayed curing properties" when it is uncured immediately after heating is completed and is cured after a specific time has passed after heating is completed. The delayed curing time may be, for example, 30 seconds to 10 hours, preferably 30 seconds to 3 hours, and more preferably 30 seconds to 2 hours. By ensuring the time until delayed curing properties are developed, operations such as lamination, tightening, and fixing can be performed.

[0065] The curing method of the curable composition of the present invention includes a method including applying the curable composition of the present invention to an adherend and then irradiating the curable composition with energy rays. For example, a curing method can be used in which the curable composition is applied to one adherend, then irradiated with energy rays to the curable composition, and then another adherend is bonded to the cured composition and cured. Other embodiments include, but are not limited to, a curing method in which the curable composition of the present invention is irradiated with energy rays, then applied to one adherend, and then another adherend is bonded to the cured composition and cured.

[0066] The curing method of the curable composition of the present invention includes a method including applying the curable composition of the present invention to an adherend and then heating the curable composition. For example, a curing method can be used in which the curable composition is applied to one adherend, the curable composition is heated, another adherend is adhered to the cured composition, and the cured composition is cured. Other embodiments include, but are not limited to, a curing method in which the curable composition of the present invention is heated, the curable composition is applied to one adherend, the other adherend is adhered to the cured composition, and the cured composition is cured. EXAMPLES

[0067] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples (hereinafter, the curable composition may be simply referred to as the composition).

[0068] [Examples 1 to 9, Comparative Examples 1 to 4] The following ingredients were prepared to prepare the composition:

[0069] Component (A): A compound having a (meth)acryloyl group in the molecule 2,2-Bis[4-(methacryloxyethoxy)phenyl]propane (EO: 2.3 mol) (NK Ester BPE-80N, manufactured by Shin-Nakamura Chemical Co., Ltd.) Isobornyl methacrylate (Light Ester IB-X, manufactured by Kyoeisha Chemical Co., Ltd.) 2-Hydroxyethyl methacrylate (Light Ester HO, manufactured by Kyoeisha Chemical Co., Ltd.) Methoxydiethylene glycol methacrylate (NK Ester M-20G, manufactured by Shin-Nakamura Chemical Co., Ltd.) Neopentyl glycol dimethacrylate (NK Ester NPG, manufactured by Shin-Nakamura Chemical Co., Ltd.) Neopentyl glycol diacrylate (NK Ester A-NPG, manufactured by Shin-Nakamura Chemical Co., Ltd.) Trimethylolpropane trimethacrylate (TMPT, manufactured by Shin-Nakamura Chemical Co., Ltd.) (B) Ingredient: Saccharin Saccharin (reagent) Component (C): Cationic catalyst Component (C-1): Photocation catalyst In the above formula 2, R - is a hexafluorophosphate salt (CPI-100P, manufactured by San-Apro Co., Ltd., solid content 50% by mass) Component (C-2): Thermal cationic catalyst ·Quaternary ammonium salt blocked with tetrakis(perfluorophenyl)borate anion (K-PURE CXC-1821, King Industries) Component (D): Radical polymerization accelerator 1,2,3,4-Tetrahydroquinoline (reagent) organic peroxide Cumene hydroperoxide (Percumyl (registered trademark) H-80, manufactured by NOF Corporation) Chelating Agents Ethylenediamine-N,N,N',N'-tetraacetic acid disodium salt dihydrate (solid at 25°C) (2NA (EDTA·2Na) manufactured by Dojin Chemical Laboratory Co., Ltd.) [Preparation of compositions of Examples 1 to 5 and Comparative Examples 1 to 4] Components (A) to (D), a chelating agent, and an organic peroxide were weighed and placed in a stirring vessel and stirred for 60 minutes in a darkened state to obtain compositions of Examples 1 to 5 and Comparative Examples 1 to 4. Detailed preparation amounts are shown in Tables 1 and 2 below, and all values ​​are expressed in parts by mass. Here, the composition shown in Table 1 contains component (C-1): a photocation catalyst as component (C), and the composition shown in Table 2 contains component (C-2): a thermal cationic catalyst as component (C).

[0070] [Table 1]

[0071] [Table 2]

[0072] The delayed curing property was confirmed for the compositions of Examples 1 and 2, Comparative Examples 1 and 2, and Example 5 according to Table 3 and the following working method. As shown in FIG. 1, 0.02 g of the composition was dropped onto the surface of a slide glass having a length of 75 mm, a width of 25 mm, and a thickness of 1 mm. Another slide glass was placed on top of the other slide glass at a right angle, and fixed with a fixing jig 2 so that the bonding area was 25 mm x 25 mm. The test piece 1 thus obtained was irradiated with light (or not irradiated) from a vertical direction to the surface of the slide glass on which the composition was placed, using a spot irradiator under the specific light irradiation conditions in Table 3. At this time, a high-pressure mercury lamp was used as the light source. After the light irradiation was stopped, the sample was left to stand according to the leaving temperature in Table 3. Here, glass was used as the material of the adherend because it was thought that metal could not be used because the composition of Comparative Example 2 may exhibit anaerobic curing property. The delayed curing time was confirmed as follows. Immediately after the light irradiation was stopped, curing was confirmed by measurement with a digital force gauge in the shear direction every minute for the first 10 minutes after the light irradiation was stopped, and every 10 minutes thereafter up to a maximum of 60 minutes. That is, a force of 30 N was applied in the direction of head movement 4 using the head 3 of the digital force gauge, and the time at which it was first confirmed that the slide glass was fixed was recorded as the delayed curing time. The results are summarized in Table 3 below. Here, the light irradiation condition of "none" indicates that no energy rays were irradiated. When curing was not confirmed, it is recorded as "x". The delayed curing time is preferably 30 seconds to 10 hours.

[0073] [Table 3]

[0074] The delayed curing property was confirmed for the compositions of Examples 3 and 4 and Comparative Examples 3 and 4 according to the following working method in accordance with Table 4. As shown in FIG. 1, 0.02 g of the composition was dropped onto the surface of a slide glass having a length of 75 mm, a width of 25 mm, and a thickness of 1 mm. The two slide glasses were stacked at right angles and fixed with a fixing jig 2 so that the bonding area of ​​another slide glass was 25 mm x 25 mm. The test piece 1 thus obtained was placed on a hot plate set under heating conditions and heated at a specific temperature and time in Table 4. After stopping the heating, the test piece was left in accordance with the leaving temperature in Table 4. After that, it was confirmed that the test piece 1 was at 25°C, and the hardening was confirmed by measuring the hardening by applying a force to the other slide glass in the shear direction using a digital force gauge while one slide glass was fixed. That is, it was confirmed whether the slide glass was fixed when a force of 30 N was applied in the moving direction 4 of the head using the head 3 of the digital force gauge. The delayed curing time was confirmed as follows. Hardening was confirmed immediately after the end of heating and every hour after the end of heating for up to 6 hours, and the time at which it was first confirmed that the slide glass was fixed was recorded as the delayed hardening time. The results are summarized in Table 4 below. If hardening was not confirmed, it is recorded as "X". The delayed hardening time is preferably 30 seconds to 10 hours.

[0075] [Table 4]

[0076] In Tables 1 and 3, Examples 1, 2, and 5 were confirmed to have delayed curing properties by light if they contained components (A) to (C) as essential components, regardless of the presence or absence of an organic peroxide. On the other hand, Comparative Example 1 did not contain saccharin, and Comparative Example 2 did not contain a photocation catalyst or a thermal cationic catalyst, so delayed curing properties were not confirmed in these cases. Comparative Example 2 is a composition that exhibits anaerobic curing properties, but since the adherend is glass, metal ions are not generated and the composition does not cure.

[0077] In addition, a comparison between Example 1 and Example 5 shows that Example 1, which does not contain an organic peroxide, has a longer delayed curing time. When no organic peroxide is used, as in Example 1, delayed curing properties can be more easily expressed. Therefore, a desired delayed curing time can be more easily obtained.

[0078] In Tables 2 and 4, it was confirmed that Examples 3 and 4 exhibited delayed curing properties due to heat, and further confirmed that the time of delayed curing changed depending on the presence or absence of component (D) and the atmospheric temperature. On the other hand, Comparative Example 3 did not contain a thermal cationic catalyst, and Comparative Example 4 did not contain saccharin, so delayed curing properties due to atmospheric temperature could not be confirmed in these cases.

[0079] [Preparation of compositions of Examples 6 to 9] Components (A) to (C) and a chelating agent were weighed and placed in a stirring vessel, and stirred for 60 minutes in a darkened state to obtain compositions of Examples 6 to 9. Detailed preparation amounts are shown in Table 5 below, and all values ​​are expressed in parts by mass. Here, the compositions shown in Table 5 contain component (C-1): a photocation catalyst, as component (C).

[0080] [Table 5]

[0081] The delayed curing property of the compositions of Examples 6 to 9 was confirmed according to the following working method in accordance with Table 6 below. As shown in FIG. 1, 0.02 g of the composition was dropped onto the surface of a slide glass having a length of 75 mm, a width of 25 mm, and a thickness of 1 mm. Another slide glass was placed on top of the other slide glass at a right angle, and fixed with a fixture 2 so that the bonding area was 25 mm x 25 mm. The test piece 1 thus obtained was irradiated with light from a vertical direction to the surface of the slide glass on which the composition was placed using a spot irradiator under the specific light irradiation conditions in Table 6 (or was not irradiated). At this time, a high-pressure mercury lamp was used as the light source. After the light irradiation was stopped, the sample was left to stand according to the leaving temperature in Table 6. The delayed curing time was confirmed as follows. Immediately after the light irradiation was stopped, the curing was confirmed by measuring with a digital force gauge in the shear direction every minute for the first 10 minutes after the light irradiation was stopped, every 10 minutes after 10 minutes until 60 minutes, and every hour after 60 minutes up to 6 hours. That is, a force of 30 N was applied in the direction of movement 4 of the head using the digital force gauge, and the time when it was first confirmed that the slide glass was fixed was recorded as the delayed curing time. The results are summarized in Table 6. Here, the light irradiation condition of "none" indicates that no energy rays were irradiated. When curing was not confirmed, it is recorded as "x". The delayed curing time is preferably 30 seconds to 10 hours, and more preferably 30 seconds to 3 hours.

[0082] [Table 6]

[0083] In Tables 5 and 6, Examples 6 to 9 all contained components (A) to (C), and were confirmed to have delayed curing properties due to light. Examples 6 to 9 all used a (meth)acrylic monomer as component (A), but Examples 7 to 9, which used a difunctional or trifunctional monomer, tended to have shorter delayed curing times than Example 6, which used a monofunctional monomer.

[0084] In particular, Example 9, which used a trifunctional methacrylic monomer, had a shorter delayed curing time than Example 7, which used a difunctional methacrylic monomer. Among the difunctional (meth)acrylic monomers, Example 8, which used an acrylic monomer, took a shorter time to cure than Example 7, which used a methacrylate monomer, and is considered to have a higher reactivity.

[0085] Furthermore, it was found that Examples 1 and 2, which mainly used BPE-80N, a (meth)acrylic monomer having a rigid bisphenol skeleton, as the component (A), tended to cure more easily than Examples 6 to 9, which used a chain-like (meth)acrylic monomer.

[0086] As shown in the above Examples 1 to 9, it was confirmed that by controlling the structure of the main skeleton of the component (A), the number of (meth)acryloyl groups, etc., a curable composition that provides a desired delayed curing time can be obtained. [Industrial Applicability]

[0087] The curable composition of the present invention exhibits stable and controllable delayed curing properties, which ensures a delayed curing time, and thus enables operations such as lamination, fastening, and fixing to be performed regardless of whether the adherend is transparent or non-transparent, and can be applied in various fields.

[0088] This application is based on Japanese Patent Application No. 2019-213030 filed on November 26, 2019, the disclosure of which is incorporated by reference in its entirety. [Explanation of symbols]

[0089] 1: Test piece 2: Fixture 3: Digital force gauge head (digital force gauge body omitted) 4: Head movement direction

Claims

1. A curable composition comprising components (A) to (C) and not containing an organic peroxide: Component (A): a compound having a (meth)acryloyl group in the molecule (B) Component: Saccharin Component (C): A photocation catalyst as the component (C-1) (however, excluding metallocene complexes in which the coordinated metal is a transition metal selected from Groups VIII, Ib, and IIb, β-diketone metal complexes in which the coordinated metal is a transition metal selected from Groups VIII, Ib, and IIb, and phthalocyanine metal complexes in which the coordinated metal is a transition metal selected from Groups VIII, Ib, and IIb).

2. Curable composition containing components (A) to (D): Component (A): a compound having a (meth)acryloyl group in the molecule (B) Component: Saccharin Component (C): Component (C-2) is a thermal cationic catalyst Component (D): a radical polymerization accelerator.

3. Curable composition containing components (A) to (D): Component (A): a compound having a (meth)acryloyl group in the molecule (B) Component: Saccharin Component (C): A photocation catalyst as component (C-1) and a thermal cationic catalyst as component (C-2) Component (D): a radical polymerization accelerator.

4. A curable composition comprising components (A) to (C) and not containing an organic peroxide: Component (A): a compound having a (meth)acryloyl group in the molecule (B) Component: Saccharin Component (C): A photocation catalyst which is a salt consisting of a cation species selected from the group consisting of iodonium-based cation species and sulfonium-based cation species, and an anion species selected from the group consisting of phosphorus-based anion species, boron-based anion species, antimony-based anion species, arsenic-based anion species, and sulfonate-based anion species, as a component (C-1).

5. The curable composition according to claim 1 or 4, further comprising a radical polymerization accelerator as component (D).

6. The curable composition according to claim 2 , 3 or 5 , wherein the component (D) is an amine compound other than the component (B).

7. The curable composition according to claim 2 or 3, which is free of organic peroxides.

8. The curable composition according to any one of claims 1, 3, and 4, wherein the component (C-1) is a compound represented by the following formula 2: 【Chemistry 1】 In formula 2, R − is an anion selected from the group consisting of hexafluoroantimonate, tetrafluoroborate, hexafluorophosphate, hexafluoroarsenate, hexachloroantimonate, trifluoromethanesulfonate, and fluorosulfonate.

9. The curable composition according to claim 1 or 4, which is uncured immediately after the end of irradiation with energy rays, and which is cured 30 seconds to 10 hours after the end of irradiation with energy rays.

10. The curable composition according to claim 2, which is uncured immediately after the end of heating and which cures 30 seconds to 10 hours after the end of heating.

11. The curable composition according to claim 3, which is uncured immediately after the end of the energy ray irradiation or the end of the heating, and which is cured 30 seconds to 10 hours after the end of the energy ray irradiation or the end of the heating.

12. A curing method comprising applying the curable composition according to claim 9 or 11 to an adherend, and then irradiating the curable composition with energy rays.

13. A curing method comprising applying the curable composition according to claim 10 or 11 to an adherend and then heating the curable composition.

Citation Information

Patent Citations

  • Method of sealing between or adhering surfaces and anaerobic adhesive composition used therefor

    JP1994108013A

  • Dark-reaction curable composition and its curing

    JP1999050014A

  • Anaerobic curable composition

    JP2017214499A